Higher Frequency of Extra-Pair Offspring in Urban Than Forest Broods of Great Tits (Parus major) - Pipoly, Ivett; Szabó, Krisztián; Bókony, Veronika; Preiszner, Bálint; Seress, Gábor; Vincze, Erno; Schroeder, Julia; Liker, András (Frontiers in Ecology and Evolution, 2019)
Urbanization increasingly changes the ecological conditions for wild animal populations, influencing their demography, reproduction, and behaviour. While studies on the ecological consequences of urbanization frequently document a reduced number and poorer body condition of offspring in urban than in non-urban bird populations, consequences for other components of reproduction are rarely investigated. Mating with partners outside the social pair-bond is widespread in birds, and although theory predicts that the occurrence of extra-pair fertilizations (EPF) may be sensitive to the altered ecological conditions of cities, the effect of urbanization on EPF is poorly known. Here we used data from two urban and two forest populations collected over three years to test whether the frequency of extra-pair offspring (EPO) in great tit broods differed between the habitats. We found that significantly more broods contained EPO in urban habitats (48.9 %) than in forests (24.4 %). In broods with EPO, the number and proportion of EPO was similar in urban and forest broods. These results suggest that females that live in urban habitats are more likely to engage in EPF than those living in forests. Urban environments may either 1) provide more spatiotemporal opportunities to EPF because of higher breeding density and lower or more constant caterpillar supply in cities compared to natural habitats, or 2) enhance the benefits of EPF via increased fertility or due to disrupted quality signals caused by anthropogenic pollution. In addition, 3) females with higher propensity to engage in EPF may more likely settle in urban habitats.